(NnAWDIWOWIVINA OBITEL)QÆ KOZACXKA(B. (NsERÆQ LISTÆWOK DO (B400-(NRÆ^^Q oNUTSXKOÇ CERKWI (B/s)E - (NgAWRIL@K(B, (Nm(B. (Nw(B.s ((NmAR)QÆQ wASILÆWNA(B)s)E; (NwASKAN(B, (Nw(B. (Nw(B.s ((NwASILX wASILXOWI^(B)s; (NdEM^ENKO(B, (Nw(B. (Ng(B.s ((Nw)QÆTALÆJ gRIGOROWI^(B)s)E; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s; (NdOWBU[(B, (No(B. )Qæ.s)E ((NoLEKSANDR )QæWANOWI^(B)s)E; (NkRISXKO(B, (Nl(B.s ((Nl)QÆLÆQ(B)s)E; (NkU[N)QÆR(B, (N`(B. (Na(B.s)E ((N`R)QÆJ aKSENTÆJOWI^(B)s)E; (NpAN^UK(B, (Ns(B. (Nm(B.s ((NsTEPAN mIHAJLOWI^(B)s; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s ((N~ERN)QÆWCÆ (B:s)E (NrODOW)QÆD(B,s)E, 2022)
(NsER)QÆQ LISTÆWOK (B"(NnADIWOWIVINA OBITELÆ KOZACXKA(B" (NPRISWQ^ENA (B400-(NRÆ^^@ oNUTSXKOÇ CERKWI(B, (N]O U wÆKNQNSXKÆJ GROMADÆ NA bUKWINÆ(B. (NcE WÆR[Æ(B-(NPRISWQTI KOZACXKÆJ CERKWÆ(B, (NQKA WISO^ÆLA U CENTRÆ oNUTA QK sIMWOL(B, (NQK oBEREG(B, (NQK wÆRA U NEZNI]ENNÆSTX(B. (NbUKOWINSXKÆ POETI gAWRIL@K m(B., (NwASKAN w(B., (NdEM^ENKO w(B., (NdVURAN w(B., (NdOWBU[ o(B., (NkRISXKO l(B., (NkU[NÆR `(B., (NpAN^UK s(B. (NWOZNOSQTX OSANNU CÆJ WIZNA^NÆJ PAM(B'(NQTCÆ STAROWINI(B.s)E
(NsP)QÆLXNIJ PROÃKT ~ERNÆWECXKOÇ OBLASNOÇ ORGANÆZACÆÇ nACÆONALXNOÇ SPÆLKI PISXMENNIKÆW uKRAÇNI Æ wÆKNQNSXKOÇ tgs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKAs)E -- (NpOEZ)QÆQ(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E